Genome sequencing provides new insights on the distribution of Erwinia amylovora lineages in northern Italy. Issue 4 (28th April 2022) - Albanese, Davide; Cainelli, Christian; Gualandri, Valeria; Larger, Simone; Pindo, Massimo; Donati, Claudio
Summary: Erwinia amylovora is a Gram‐negative bacterium that colonizes a wide variety of plant species causing recurrent local outbreaks of fire blight in crops of the Rosaceae family. Recent genomic surveys have documented the limited genomic diversity of this species, possibly related to a recent evolutionary bottleneck and a strong correlation between geography and phylogenetic structure of the species. Despite its economic importance, little is known about the genetic variability of co‐circulating strains during local outbreaks. Here, we report the genome sequences of 82 isolates of E . amylovora, collected from different host plants in a period of 16 years in Trentino, a small region in the Northeastern Italian Alps that has been characterized by recurrent outbreaks of fire blight in apple orchards. While the genome isolated before 2018 are closely related to other strains already present in Europe, we found a novel subclade composed only by isolates that were sampled starting from 2018 and demonstrate that the endemic population of this pathogen can be composed by mixture of strains.